Virulence, Antibiotic Resistance and Cytotoxic Effects of Lactococcus lactis Isolated from Chinese Cows with Clinical Mastitis on MAC-T Cells - Tiancheng Wang; Fan Wu; Tao Du; Xiaodan Jiang; Shuhong Liu; Yiru Cheng; Jianmin Hu (Microorganisms)
Lactococcus lactis (L. lactis) is a pathogenic Gram-positive, catalase-negative coccobacillus (GPCN) associated with bovine mastitis. In this study, nine strains of L. lactis were successfully isolated and characterized from 457 milk samples from cows with clinical mastitis in China. All isolates exhibited a high degree of susceptibility to marbofloxacin and vancomycin. A series of molecular and cell biological techniques were used to explore the biological characteristics and pathogenicity of these isolates. The virulence gene profiles of the isolates were analyzed using whole genome resequencing combined with polymerase chain reaction (PCR) to elucidate the differences in virulence gene expression between isolates. To provide a more visual demonstration of the pathogenic effect of L. lactis on bovine mammary epithelial cells, an in vitro infection model was established using MAC-T cells. The results showed that L. lactis rapidly adhered to the surface of bovine mammary epithelial cells and significantly induced the release of lactate dehydrogenase, suggesting that the cell membranes might be damaged. Ultrastructural observations showed that L. lactis not only adhered to MAC-T cells, but also invaded the cells through a perforation mechanism, leading to a cascade of organelle damage, including mitochondrial swelling and ribosome detachment from the endoplasmic reticulum. The objective of this study was to provide strong evidence for the cytotoxic effects of L. lactis on bovine mammary epithelial cells. Based on this research, a prevention and treatment strategy for L. lactis as well as major pathogenic mastitis bacteria should be established, and there is a need for continuous monitoring.